(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters:Chapter one - definition of the researchThis chapter included the introduction and the importance of the research, as the athletics competitions and their importance in Olympia were addressed, and the sprinting events are considered one of the most exciting and exciting athletics activities because of their strong competition, and the (100) meter race is one of the fast and short running competitions. Whoever wins is the one who achieves the least time, whether it is in running (100) meters or running a marathon (195.42) km. Therefore, the use of information and scientific knowledge is the only way to overcome this severe shortcoming in achievement in fast running events. Hence The importance of the research came in an attempt to employ the role of sports training by developing an appropriate training curriculum to develop maximum speed and speed endurance, and thus achieve a 100-meter run.